2021
DOI: 10.3390/rs13173501
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Land Use and Land Cover Change Using Time-Series Data and Random Forest in North Korea

Abstract: North Korea being one of the most degraded forests globally has recently been emphasizing in forest restoration. Monitoring the trend of forest restoration in North Korea has important reference significance for regional environmental management and ecological security. Thus, this study constructed and analyzed a time-series land use land cover (LULC) map to identify the LULC changes (LULCCs) over extensive periods across North Korea and understand the forest change trends. The analysis of LULC used Landsat mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Meanwhile, high producer's classification accuracies were identified for the class of water body (100%), forest (80%), and builtup area (70%). The result suggests that high accuracy is gained for the stable class such as water body (Piao et al, 2021).…”
Section: Key Classification In Sentinel-1mentioning
confidence: 94%
See 2 more Smart Citations
“…Meanwhile, high producer's classification accuracies were identified for the class of water body (100%), forest (80%), and builtup area (70%). The result suggests that high accuracy is gained for the stable class such as water body (Piao et al, 2021).…”
Section: Key Classification In Sentinel-1mentioning
confidence: 94%
“…Remote sensing technology plays a role in extracting and monitoring land cover which is known to have variations in spectral, temporal, and spatial resolution. Remote sensing with optical sensors has been widely used for land monitoring (Gumma et al, 2019;Piao et al, 2021;Sarono et al, 2015), but the image quality and accuracy of mapping using this sensor depends on atmospheric conditions. Primarily the use of optical data is a challenge due to high cloud interference in tropical countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian yang dilakukan oleh (Gandharum et al, 2022;Piao et al, 2021;Singha et al, 2019) menunjukan hasil penelitian bahwa penggunaan RF pada platform GEE dalam pemetaan penggunaan lahan dapat menghasilkan peta dengan akurasi tinggi dengan OA mencapai 92.6%. Hasil penelitian ini memiliki konsistensi dengan penelitian lain di mana gambar dan indeks gabungan dapat mencapai kurasi klasifikasi yang lebih tinggi daripada penggunaan hasil dari klasifikasi tunggal (Carrasco et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Sharma et al, (2016) utilized high-resolution imagery from the Landsat 8 Operational Land Imager to generate an LCLU map with a resolution of 30 m for Japan covering 2013-2015 [23]. Based on data from the same source, Piao et al (2021) reported changes in the forest cover of North Korea using 18 LCLU maps from 2001 to 2018 [24], and Hansen et al (2020) identified the tropical forest changes during same period [25]. In contrast, Seo et al (2014) mapped the landscape in the catchment of Haean in South Korea and documented the LCLU types for 2009-2011 via annual field campaigns [26].…”
Section: Introductionmentioning
confidence: 99%